2011
DOI: 10.1097/pep.0b013e318227ca0f
|View full text |Cite
|
Sign up to set email alerts
|

An Intensive Virtual Reality Program Improves Functional Balance and Mobility of Adolescents With Cerebral Palsy

Abstract: Functional balance and mobility in adolescents with cerebral palsy classified at GMFCS level I improve with intense, short duration VR intervention, and changes are maintained at 1-month posttraining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 25 publications
3
74
0
6
Order By: Relevance
“…Hence, findings of the current work are consistent with those found by Brien [30], Deutsch [19], Luna-Oliva [18], Tarakci [4], JELSMA [29], and Morris [31] conducted using different balance tests in population of children with cerebral palsy. However, unlike findings in the current research, Ramstrand's work suggested lack of impact of implementing exercises in virtual reality on improvement of balance in children with cerebral palsy [32].…”
Section: Resultssupporting
confidence: 82%
“…Hence, findings of the current work are consistent with those found by Brien [30], Deutsch [19], Luna-Oliva [18], Tarakci [4], JELSMA [29], and Morris [31] conducted using different balance tests in population of children with cerebral palsy. However, unlike findings in the current research, Ramstrand's work suggested lack of impact of implementing exercises in virtual reality on improvement of balance in children with cerebral palsy [32].…”
Section: Resultssupporting
confidence: 82%
“…Results from their study support two major findings: (i) the data suggest that functional balance and mobility in adolescents with CP can improve with an intense, short duration VR intervention and (ii) improvements in outcome measures are maintained for at least one month following VR training. 14 It is difficult to say whether the changes observed in gross motor function were due to the training program, to a learning effect or to natural changes. 12 However, these results indicate that there may be some potential for training with a VR environment (like Nintendo Wii) to have an impact on gross motor function, and research studies should be conducted to explore this hypothesis.…”
Section: Brien Et Almentioning
confidence: 99%
“…Straker et al 6 , Gordon et al 12 and Brien et al 14 claim that virtual reality can improve motor ability in this population.…”
mentioning
confidence: 99%
“…Furthermore, there is now a growing evidence base to support their use in a variety of different rehabilitation applications including mobility and aerobic fitness [13][14][15], post-stroke rehabilitation of hand-arm function [16][17][18], balance [14,[19][20][21], pain distraction while undergoing treatment/therapy [22], and treatment of amblyopia ("lazy eye") [23].…”
Section: Introductionmentioning
confidence: 99%